Administración financiera de las empresas carboníferas (2020)
The main objective of the research was to analyze the financial management of coal companies in the northern zone of Colombia. Methodologically, the research was descriptive, with a non-experimental design, descriptive and field transectional. The population consisted of 18, reporting units were the personnel assigned to the financial management department of the coal companies in the northern zone of Colombia. For the collection of data, a questionnaire was used consisting of fifty-four (54) Likert-type questions, which was validated by five (5) experts and the reliability determined by the Cronbach’s Alpha coefficient with a value of 0.86. In relation to the obtained results, it was concluded that the variable financial administration allows to conclude that this has a very high compliance level in the established scale, where it is observed that the coal companies of the northern zone of Colombia. The presented results of the dimensions that make up the financial administration variable allow to conclude that this has a high compliance in the established scale, where it is observed that in the coal companies where it is observed that in the coal companies it applies a series of actions which are focused to achieve a specific financial purpose, optimizing financial resources to achieve the objectives of the organization with greater efficiency and profitability.